The Role of Librarians in Improving Information Literacy in the Millennial Generation: Case Study of Library Potensi Utama University - Idzhari Rahman; Fauzan Hidayatullah; Fatri Ardiansyah (Literatify: Trends in Library Developments, 2023)
Librarians are required to be critical in having information literacy skills on how to empower the information they have. Therefore, the purpose of this article is to explain and discuss how the challenges of librarians in improving information literacy and information tracing skills of the millennial generation in the University Library Main Potential in meeting their information needs information literacy as a process of acquiring knowledge. The qualitative approach in this case is actually a research procedure that produces descriptive data in the form of written or spoken words of people and observable behavior. Information literacy skills of Librarians in University Libraries The main potential in the implementation of excellent services in libraries is interpreted as a form of cognitive skills that are reflected in the ability to identify, Understand and interpret the information obtained to be transformed into users, as well as productive activities that are able to provide social, economic and welfare benefits for users.